Women’s Body Mass Index (BMI): An Analysis of The Covid 19 Lockdown Case - Khan, Nahreen Islam; Nawer, Afra (The Jahangirnagar Review, 2024)
The global coronavirus disease pandemic, or COVID-19, began to spread in 2020. To avoid infection, several countries have implemented lockdown or stay-at-home regulations. From March to May 2020, Bangladesh was in lockdown, with internal travel limited. Women’s health may be harmed by such long and strict confinement. The goal of this study was to compare women’s health before and during the COVID-19 pandemic in order to estimate the influence of the pandemic on their health. A prospective longitudinal study in two areas in Dhaka city was conducted. The women in the research were married but not pregnant. Overall 20 non-pregnant women had regular checkups before and during the COVID-19 pandemic, from October 2019 to January 2020 and October 2020, respectively. The medians of body mass index were compared to those during the 2019 health checkup. Their health may have been harmed by the lack of physical activity and other inconveniences brought on by their long confinement. This study has a variety of sociodemographic characteristics, including reported mental health issues, sleep problems, physical problems, and social behaviors that may be related to BMI, eating patterns, and physical activity. Additionally, there is compelling evidence that their physical and routine activity, weight, and other relevant factors are altering. Therefore, the current study aimed to highlight perceived changes in BMI, eating patterns, and the physical activity level among married women in Bangladesh between "before" and "during" the COVID-19 lockdown. There were elements of both qualitative and quantitative research procedures incorporated into the study, making it a mixed-methods investigation. The research was quantitative in nature, and its purpose was to quantify the data that was gathered and to generalize the findings from a sample to the entire population. In addition, it was qualitative since the research endeavored to derive more profound interpretations from the findings by employing qualitative methods such as conducting in-depth interviews. The majority of the processing and evaluation of the information that was received from the Google Forms questions was done through the use of electronic methods. All of the information that was obtained from the surveys was manually entered into the spreadsheet software that was provided by Google Excel. Also, the program gave the researchers the ability to select a large number of fields and construct a variety of charts, which allowed them to investigate the correlations between a number of different variables.